Assessing the dynamics of cost of equity: a critical literatures of its determinants, models, and implications for financial management - Saidin, Saidatunur Fauzi; Al-qadi, Maher Azzam Ghaleb; Abdul-hamid, Mohamad Ali; Abdelrehim, Mahmoud (International Journal of Academic Accounting, Finance & Management Research(IJAAFMR), 2024)
This paper conducts a comprehensive analysis of the Cost of Equity Capital (COE), crucial for guiding corporate finance and investment decisions. It delves into a variety of models for estimating COE, including the Residual Income Model (RIM), Price/Earnings to Growth (PEG) ratio, and Capital Asset Pricing Model (CAPM), each examined for its theoretical basis, assumptions, and relevance to market expectations and corporate performance. Beyond traditional financial metrics, the study expands to consider the impact of corporate governance and non-financial determinants such as corporate social responsibility (CSR) and environmental sustainability on COE. It highlights how these factors significantly influence investor perceptions and risk evaluations, thereby affecting the COE. Through analysis of empirical research, the paper illustrates the relationship between strong governance, CSR initiatives, and reduced equity costs, advocating for an integrated approach that balances financial performance with societal contributions. The findings suggest a need for further exploration into the interactions between financial and non-financial factors to enhance COE estimation methods and encourage corporate practices that promote sustainable development and social welfare. This synthesis underscores the complexity of COE estimation and calls for a holistic valuation strategy that aligns economic objectives with broader societal goals.